Higher education reforms institutional restructuring in Asia - Varghese, N.V. (Paris UNESCO, International Institute for Educational Planning, 2009)
"Reforms in higher education are very often driven by both financial considerations and by efforts to improve the quality and relevance of courses and programmes of study. Privatization of services, corporatization of operations, and re-orientation of curriculum and student assessment are common recent reform measures in higher education. As a result of such reforms, institutions of higher education have become more managerial and entrepreneurial in their approach, as well as in their operations. Although these reform measures were initially introduced on a small scale, they have cumulatively led to dramatic transformations in the organization of university activities leading to a restructuring of the institutions. Institutions have become progressively more independent from the government and have introduced new governance and management structures. This book, based on IIEP research carried out in Indonesia, Malaysia, Mongolia, Thailand and Vietnam, examines the trends in institutional restructuring in countries of the Asian region."--www.iiep.unesco.org.
1. Institutional restructuring of higher education in Asia : an overview / by N.V. Varghese -- 2. Gadjah Mada University, Indonesia / by Sahid Susanto and M. Nizam -- 3. Universiti Kebangsaan Malaysia / by Muhammad Yahaya and Imran Ho Abdullah -- 4. The Mongolian University of Science and Technology / by Yadmaa Narantsetseg -- 5. King Mongkut's University of Technology Thonburi, Thailand / by Banterng Suwantragul -- 6. Hue University, Vietnam / by Huyhn Dinh Chien.
Keywords: Education, Higher -- Asia; Educational change -- Asia; Organizational change -- Asia